2005
DOI: 10.1111/j.1523-1755.2005.67136.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic demand and renal mass supply affecting the early graft function after living donor kidney transplantation

Abstract: During living donor and recipient matching, both the potential sizes of the donated kidney and the recipient should be considered in terms of the early graft function after transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 24 publications
(12 reference statements)
0
35
0
Order By: Relevance
“…Selection has been made case-by-case, considering the functional ratio by 99mTcDTPA renal scan and the estimated functional demands of both donor and recipient. 9 Total renal function and anatomic characteristics of the donor's two kidneys were discussed during a conference with transplant surgeons, nephrologists, and urologists prior to transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Selection has been made case-by-case, considering the functional ratio by 99mTcDTPA renal scan and the estimated functional demands of both donor and recipient. 9 Total renal function and anatomic characteristics of the donor's two kidneys were discussed during a conference with transplant surgeons, nephrologists, and urologists prior to transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Linear regression demonstrated that the independent predictors of recipient posttransplantation Scr included the ratio of graft weight to recipient body weight, the ratio of graft weight to recipient BSA, and the ratio of graft weight to recipient BMI, as previously reported. 6 Among the ratios, the absolute value of the beta-coefficient (P ϭ .024, beta-coefficient ϭ Ϫ11.501, 95% CI ϭ Ϫ0.253-Ϫ0.018) of the ratio of graft weight to recipient BSA was the highest, implicating that the ratio would be most predictive for the Scr after transplantation.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study demonstrated that independent predictors of recipient posttransplantation Scr included the ratio of graft weight to recipient body weight, the ratio of graft weight to recipient body surface area (BSA), and the ratio of graft weight to recipient body mass index (BMI). 6 Prediction of posttransplantation Scr of recipients should be possible purely based on the balance between the metabolic demands of recipients and the renal mass supplies from the donor. However, it can be influenced by many insults, such as ischemia/ reperfusion damages, rejection episodes, nephrotoxic immunosuppressants, diabetes, hypertension, infection, and other complications, especially in the early period posttransplantation.…”
Section: G Raft Function After Kidney Transplantation Ismentioning
confidence: 99%
“…Most of all, sufficient functional nephron mass for the recipient is important for early graft function. 5 An insufficient nephron mass might fail to meet the metabolic demands of a kidney recipient leading hyperfiltration, which has been suggested to be an important factor in the progression of kidney disease. 4,8 In this study, fractional creatinine clearance of the donated kidney showed a significant correlation with early graft function within 6 month after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…In order to prevent hyperfiltration, it is important to initially provide an adequate functioning nephron number to meet the metabolic demands of a recipient as well as to allow adequate nephron mass in case of rejection episodes, nephrotoxic drugs, or other potential injuries. 5,6 During the preoperative evaluation of a potential kidney donor, it is necessary to estimate the renal function of the donated kidney compared with the metabolic needs of the recipient. In this study, we determined the correlation between the preoperative function of the donated kidney and the postoperative graft function of the recipient at 1 year posttransplantation.…”
Section: Arly Graft Function In Renal Transplant Recip-mentioning
confidence: 99%